Beyond the Biomedical Paradigm: Generating a Spiritual Vision of Ageing - Kimble, Melvin (Journal of religious gerontology, 2002)
The time has come to enlarge our understanding of what an ageing older person truly is. What is called for is an approach to ageing and its multiple processes that moves beyond an empirical research model, which is limited to a positivistic focus on the bio-medical and social conditions of ageing. The spiritual dimension of the individual as well as the physical and social need to be acknowledged and valued in any definition of human existence. A segmental approach to the ageing process can only result on a reductionistic, one-dimensional caricature of the older person. There is an imperative need for the inclusion of the spiritual dimension in the study of ageing and its meaning. By issuing a call for a new wholistic paradigm that moves beyond the bio-medical model, and understanding the personhood is affirmed which includes a person's capacity to find meaning in life, indeed, even in ageing, suffering and dying.